2018
DOI: 10.2478/fhort-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Field and laboratory screening of anthurium cultivars for resistance to foliar bacterial blight and the induced activities of defence-related enzymes

Abstract: Bacterial blight (BB) caused by Xanthomonas axonopodis pv. dieffenbachiae (Xad) is the most destructive disease of ornamental anthurium. In the present study, foliar resistance of 21 anthurium cultivars were assessed under shaded field and laboratory conditions by injection inoculation of 3 × 10 8 cfu/ml Xad; disease severity was evaluated using a pretransformed rating scale after symptoms survey. Then six selected cultivars with different resistance levels were evaluated for the induced activities of six defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Superoxide dismutase (SOD), peroxidase (POD), hydroperoxidase (CAT) and ascorbate peroxidase (APX) together constitute the antioxidant system of plants to remove excess ROS under stress conditions [ 36 ]. With the increase of pathogen infection time, the SOD and APX activities of ‘BlackJack’ initially increased and then decreased, reached a maximum on the 5th day after inoculation, and were significantly higher on the 9th day than 0th day (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide dismutase (SOD), peroxidase (POD), hydroperoxidase (CAT) and ascorbate peroxidase (APX) together constitute the antioxidant system of plants to remove excess ROS under stress conditions [ 36 ]. With the increase of pathogen infection time, the SOD and APX activities of ‘BlackJack’ initially increased and then decreased, reached a maximum on the 5th day after inoculation, and were significantly higher on the 9th day than 0th day (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the phenylpropanoid pathway defense enzymes, PAL is the first enzyme that produces the precursors for lignin and phenolic secondary metabolites (Sticher et al, 1997). PPO is another key enzyme in the synthesis of phenolic compounds with antimicrobial activity (Babu et al, 2015;Jia et al, 2016;Niu et al, 2018). Muslim et al (2019) revealed that the lignin deposition in cucumber plants can prevent the pathogen Colletotrichum orbiculare infection, and also the level of total phenolics was increased in cucumber seedlings after being inoculated with the P. xanthii (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest responses is the rapid generation of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH − ), and superoxide anion (O 2− ) (Patykowski and Urbanek, 2003). ROS scavenging enzymes such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) play an essential role in regulating ROS levels and the extent of oxidative damage (Niu et al, 2018). The phenylpropanoid pathway is another defense response in higher plants (Irisarri et al, 2016;Hou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these is the generation of reactive oxygen species (ROS) and establishing a balance between ROS production and scavenging during pathogen-plant interactions [ 6 ]. ROS scavenging enzymes including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) are key components for regulating ROS levels and are also pertinent to plant disease resistance [ 7 ]. Furthermore, the phenylpropanoid pathway has been acknowledged to be important in higher plants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%